2017
DOI: 10.33546/bnj.290
|View full text |Cite
|
Sign up to set email alerts
|

Binahong Leaves (Anredera Cordifolia Tenore Steen) Extract as an Alternative Treatment for Perineal Wound Healing of Postpartum Mothers

Abstract: Background: Perineal wounds are at risk for infection, without a good treatment, perineal wound can harbor sepsis and become a chronic, long-term problem. Binahong leaves is considered as an alternative to accelerate perineal wound healing process.Objective: To determine the effect of binahong leaf extract (anredera cordifolia (tenore) steen) on perineal wound healing process in postpartum mothers.Methods: This study employed a quasy experimental study with control group posttest-only design. The study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It is observed that there is a significant difference in the duration of wound healing between the treatment group and the control group. 25 Imron and Risneni 21 showed that the longest healing time experienced by postpartum women who were given laceration treatment with povidone-iodine is ≥7 days, namely 38 respondents (95%) with an average healing time of 8 days. Meanwhile, 20 respondents (50%) who used binahong leaf decoction showed the average healing time is five days.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that there is a significant difference in the duration of wound healing between the treatment group and the control group. 25 Imron and Risneni 21 showed that the longest healing time experienced by postpartum women who were given laceration treatment with povidone-iodine is ≥7 days, namely 38 respondents (95%) with an average healing time of 8 days. Meanwhile, 20 respondents (50%) who used binahong leaf decoction showed the average healing time is five days.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian secara in vivo, daun binahong konsentrasi 20% mampu mempercepat penyatuan luka sayatan pada mencit jantan (Purwasih & Safitri, 2018). Penelitian ini serupa dengan penelitian terdahulu yang menyimpulkan bahwa sediaan ekstrak daun binahong mempercepat luka perineum menjadi kering pada ibu nifas (Aditia et al, 2017). Penelitian lain juga menyatakan spray gel binahong efektif dalam mempersingkat penyembuhan luka perineum pada ibu pasca bersalin (Chikmah et al, 2019).…”
Section: Hasil Dan Pembahasanunclassified
“…Perineal wounds occur generally after the mothers giving birth to their baby. This kind of wound is really prone to infection and may lead to serious complications if left untreated or treated in a wrong manner and unhygienically (Aditia et al, 2017).…”
Section: Burn Wound Healing Perineal Wound Healing and Diabetic Wound...mentioning
confidence: 99%
“…There are several chemical ingredients in Binahong leaves, including flavonoids, oleanolic acid, protein, ascorbic acid (Ariani, Loho, & Durry, 2014), tannins, as well as triterpenoid, alkaloid, glycoside, and steroid saponins (Kurniawan, Carolia, & Pheilia, 2014). Binahong leaves also have antimicrobial, antiinflammatory, anti-parasitic, and anti-fever properties (Aditia et al, 2017). The ascorbic acid content in this plant is crucial for the activation of the prolyl hydroxylase enzyme, which supports the stage of hydroxylation in the formation of collagen so that the wound healing process can be accelerated (Ariani, Loho, & Durry, 2014).…”
Section: Burn Wound Healing Perineal Wound Healing and Diabetic Wound...mentioning
confidence: 99%